Pendampingan Promosi Pariwisata Desa Sumber Rejo Purwosari Pasuruan (Jempinang Rafting - Zainul Rojikin, Mohammad; Nurma Yuwita (Institut Agama Islam Sunan Kalijogo Malang, 2022)
In an era of pandemics like this, tourism everywhere is subject to the same impact, a significant drop in the number of visitors and also the large losses experienced by tourism managers make it a big pr to continue to improve. In experiencing a pandemic like this, promotions must be carried out so that visitors continue to come to these tours and also the stability of managers and traders in tourist attractions remains prosperous. Therefore, the authors carry out Real Work Practices (PKN) in assisting rural tourism promotion that focuses on social media including Facebook, Instagram, Tik Tok, and news media. So that the jempinang rafting tour will be better known by people throughout Indonesia. From the use of these three media, Instagram is more dominant for promotion on social media because many social media users have created new interests, namely promotion through social media. The second is occupied by the Tik Tok application and the third is the news media.